Visual Exposure of Rock Outcrops in the Context of a Forest Disease Outbreak Simulation Based on a Canopy Height Model and Spectral Information Acquired by an Unmanned Aerial Vehicle - Balková, Marie; Bajer, Aleš; Patočka, Zdeněk; Mikita, Tomáš (MDPI AG (Multidisciplinary Digital Publishing Institute-MDPI), 2020)
This research was focused on the study of visual exposure evolution in the locality of the Drátenická skála nature monument (in the Czech Republic) and the surrounding forest complex in terms of history and through modelling for further possible stand development. The local forests underwent conversion from a natural fir-beech composition to an intensive spruce monoculture with few insect pests or windbreak events to an actual bark beetle infestation. Historic maps, landscape paintings, photographs, and orthophotos served as the basic materials for the illustration of the past situation. Further development was modelled using canopy height models and spectral properties captured by unmanned aerial vehicles (UAVs). As an example, the possible situation of total mortality among coniferous spruce trees after a bark beetle outbreak was modelled. Other options and a practical use of such preprocessed data are, for example, a model for opening and transforming the stands around the rock as one of the ongoing outcrop management trends in the protected landscape area (PLA) of Žďárské vrchy.
Keywords: canopy; image classification; orthophoto; historical maps; UAV; NDVI; digital terrain model; digital surface model